Manajemen Strategi Dalam Meningkatkan Kinerja Pegawai Puskesmas Tulung Selapan Kabupaten Ogan Komering Ilir - Telly Pauline Uliviana Siwi (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2022)
This research is strategic management in improving employee performance at Tulung Selapan Health Center, Ogan Komering Ilir Regency, with the aim of knowing (1) the strategy carried out by Tulung Selapan Health Center, Ogan Komering Ilir Regency in improving employee competence for health services. (2) Factors that support and hinder in improving the competence of employees at the Tulung Selapan Health Center, Ogan Komering Ilir Regency The research approach used in this research is the method used in this study is a qualitative research method. The definition of qualitative research is essentially observing people in their environment, interacting with them, trying to understand their language and interpretation of their surroundings. The data required includes secondary data and primary data obtained in various ways, including: Documentation, Interview (Indept Interview), Observation. The results of the analysis are (1) the strategy used to improve employee performance in health services at the Tulung Selapan Health Center by using the SO strategy, namely using strength to take advantage of opportunities. (2) Internal factors in the implementation of improving community services in Tulung Selapan, namely (a) strengths consisting of 1) Availability of facilities and infrastructure, 2) Implementation of Regional Regulations and Regulations of the Minister of Health, 3) Public awareness of the importance of health, 4) Development increasing population, 5) The role of the apparatus in providing health education, (b) weaknesses consisting of: 1) Limited Human Resources, 2) Limited knowledge of hospital administration services (health), 3) Innovation in the media very minimal information, 4) Lack of skilled personnel, 5) Limited software. And external factors, namely a) opportunities consisting of 1) public awareness about good health, 2) public awareness in the importance of administrative order, 3) globalization in the information media, 4) implementation of Regional Regulation No. 58 of 2008. b) threats consisting of from: 1) The more open the information media, 2) The tighter competition between individuals in the health sector, 3) The difficulty of implementing information systems that are applied among employees, 4) Limited human resources in the health sector, 5) The limited role of community leaders in providing health information Based on the results of the study, several things can be recommended, namely: 1) Improving the quality of employee human resources and improving software to support the interests and needs of the Health Center (2) Carrying out a strategy to survive against existing conditions, both the quality of resources and employees in order to create a conducive atmosphere.